Description of Social Media Use and Self-Esteem of Adolescents in Makassar City - Rahman, Framita; Jane, Brigita Sri; Ngandoh, Mutiara Cyesa Prasasti; Saputri, Wiwi; Tuhelelu, Puspa Akhlakul Karima (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Adolescence is a crucial period of time and very challenging period. There is an increase concern on how social media use and mental health of teenagers. In Makassar City, there is a high number of mental health in adolescence yet still rare research has been conducted to investigates about social media use and self-esteem on teenagers. The aim of this study is to give a description on how adolescence behaviour on social media use and their level of self-esteem. This research uses a quantitative study with descriptive study design. The participant was selected based on some inclusion criteria such as teenagers’ age 16-18 years old, able to speak Bahasa, stay in Makassar City and willingly to become participant. The participant was determined by using non-probability sampling using convenience sampling method. There are 118 participants on this research. Three types of instruments were used; demography questionnaire, intensity of social media use and Rosenberg Self-Esteem Scale. From 118 participants, 19 were male and 99 were female. There are 42 respondents spend more than 6 hours on social media, and 54 respondents spend 2-6 hours on social media per day. Most of the respondents use their social media for see feed (20%), give like (14%), stalking (9%), news sharing (9%) and give comment (6%). Most of the respondents have high social media use (70 respondents) and low self-esteem (66 respondents). Social media use is quite high among teenagers in Makassar City and the self-esteem is mostly low. Thus, it is important to investigate the relationship of social media use and self-esteem so that it can give a comprehensive understanding on adolescence’s mental health and wellbeing in Makassar City